CONTENT CHARACTERISTICS OF FUTURE NURSES' ENVIRONMENTAL COMPETENCE (Innovative professional education, 2025)
The essence and structural elements of the formation of ecological competence of future nurses in professional colleges are highlighted. The essence of the concept of «ecological competence» is clarified as an integrative characteristic of the personality acquired in the process of training, which determines readiness and ability of applicants for professional pre-higher education to environmental activities and is based on knowledge, skills, experience, value orientations that are formed in the process of studying disciplines of general and professional cycles. The components, criteria and indicators of the studied phenomenon and the levels of its formation in applicants for professional pre-higher education are substantiated
Keywords: vocational college, ecological competence, future nurses, professional education, sustainable development